Meningkatkan Hasil Belajar Siswa Melalui Model Pembelajaran Relating, Experiencing, Applying, Cooperating Dan Transferring (REACT) - Erwina Erwina; M. Arifuddin Jamal; Sri Hartini (Berkala Ilmiah Pendidikan Fisika, 2015)
Improve learning achievement of students grade VIII D SMPN 1 Amuntai through Relating, Experiencing, Applying, Cooperating and Transferring (REACT) model. Application of the talking method in learning activities cause students weren’t active and it result to the low of students learning achievement. This condition needs a classroom action research to improve students learning achievement through Relating, Experiencing, Applying, Cooperating and Transferring (REACT). The aim of this research is describe way to improve students learning achievement through REACT model. The specific aims are describe: (1) lesson plan feasibility, (2) students learning achievement and (3) students activities. This classroom action research use Hopkins model that consist of 2 cycles. Data were collected by observation, test and documentation. Then data were analyzed by descriptive qualitative and descriptive quantitative. This research show that: (1) lesson plan feasibility in relating included good, experiencing included good, applying included good, cooperating included good and transferring included good; (2) students learning achievement were improve from 65,00% or didn’t completed classical achievement in cycle I to 77,27% in cycle II or completed classical achievement; and (3) students activity contain questioning, propose argument/answered teacher’s questions, listen teacher’s explain and discuss task severally included good. It can be concluded that learning achievement of students grade VIII D SMPN 1 Amuntai can improve though REACT model with link a new concept to something completely familiar to students, guide students discover concept through laboratory activity, help students answered application and analysis question on worksheet, guide students to discuss in group and guide students to use their knowledge in a new context and also make students active in learning activities.